Hobbes and history - Rogers, G. A. J. (Graham Alan John), 1938-; Sorell, Tom (Routledge studies in seventeenth-century philosophy., 2000)
This collection of scholarly essays explores the relation of Hobbes' work to history as a branch of learning.